2018
DOI: 10.1177/0973217918795230
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Neonatal Emergencies Simulation Team-Training (NEST) Improves Participant’s Confidence in Dealing With Simulated Neonatal Emergencies

Abstract: Background: A traditional medical curriculum has limited emphasis on communication skills, teamworking, and human factors. Simulation-based training emphasizes these skills and positively impacts patient safety. A group of Indian neonatologists in collaboration with their UK colleagues conducted adapted Neonatal Emergencies Simulation Team-training (NEST) courses in India. Aim: To evaluate the effectiveness of NEST courses in India and analyze the participant’s feedback Methods: A total of 16 NEST courses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The data presented by Swamy et al, 19 are similar to those described in previous studies which showed that high-fidelity simulation allows participants to practice their skills in communication, assessment, diagnosis, and treatment, as well as teamwork. 20,21 Knowledge is gained when candidates develop their own hypotheses and test these against their current understanding.…”
Section: Evaluation Of the Impact Of Simulation-based Training On Nicu Crm In Indiasupporting
confidence: 83%
See 3 more Smart Citations
“…The data presented by Swamy et al, 19 are similar to those described in previous studies which showed that high-fidelity simulation allows participants to practice their skills in communication, assessment, diagnosis, and treatment, as well as teamwork. 20,21 Knowledge is gained when candidates develop their own hypotheses and test these against their current understanding.…”
Section: Evaluation Of the Impact Of Simulation-based Training On Nicu Crm In Indiasupporting
confidence: 83%
“…Course feedback was also consistent between centers. The evaluation by Swamy et al 19 demonstrates the efficacy of NEST courses in India. NEST India showcases the pioneering effort by neonatal pediatricians in a lowincome country.…”
Section: Evaluation Of the Impact Of Simulation-based Training On Nicu Crm In Indiamentioning
confidence: 99%
See 2 more Smart Citations